How to do things with words: Two seminars on the naming of functional (psychogenic, non-epileptic, dissociative, conversion, …) seizures. (December 2021) - Wardrope, Alistair; Dworetzky, Barbara A.; Barkley, Gregory L; Baslet, Gaston; Buchhalter, Jeffrey; Doss, Julia; Goldstein, Laura H.; Hallett, Mark; Kozlowska, Kasia; LaFrance.Jr, W Curt; McGonigal, Aileen; Mildon, Bridget; et al.
Highlights: An interdisciplinary review of patients' and professionals perceptions of the functions and effects of naming of psychogenic non-epileptic seizures. Presents a range of considerations for and against different choices of nomenclature. Arguments for, and a trajectory towards, consensus terminology are provided. Abstract: Amongst the most important conditions in the differential diagnosis of epilepsy is the one that manifests as paroxysms of altered behaviour, awareness, sensation or sense of bodily control in ways that often resemble epileptic seizures, but without the abnormal excessive or synchronous electrical activity in the brain that defines these. Despite this importance, there remains little agreement – and frequent debate – on what to call this condition, known inter alia as psychogenic non-epileptic seizures (PNES), dissociative seizures (DS), functional seizures (FS), non-epileptic attack disorder (NEAD), pseudoseizures, conversion disorder with seizures, and by many other labels besides. This choice of terminology is not merely academic – it affects patients' response to and understanding of their diagnosis, and their ability to navigate health care systems.This paper summarises two recent discussions hosted by the American Epilepsy Society and Functional Neurological Disorders Society on the naming of this condition. These discussions are conceptualised as the initial step of an exploration of whether it might be possible to build consensus for a new diagnostic label.